Perceived Entrepreneurial Training Needs of Trainees of Krishi Vigyan Kendras in Kerala - B. R., Gayathri; Binoo P. Bonny (Journal of Extension Education, 2021)
The present study was conducted in the state of Kerala to analyse the training needs of 100 trainees of five Krishi Vigyan Kendras (KVK). The findings indicated that the packaging & marketing of mushroom and post harvest handling value addition were the most preferred training areas by the KVK trainees in mushroom production. In apiculture, honey extraction essential operations was perceived as the most needed area of training. In the area of value addition of fruits and vegetables, technology upgradation and packaging marketing techniques were the most preferred areas by the trainees. Relational analysis revealed that socio-economic variables like educational status and annual income, communication variables like extension contact and mass media exposure and entrepreneurial variables like entrepreneurial intention, entrepreneurial need, entrepreneurial capacity, innovativeness, achievement motivation, decision making ability, risk orientation, self confidence, cosmopoliteness and economic motivation were found positively and significantly correlated with training needs. The KVKs should take concrete efforts to organize need based entrepreneurship development training programmes to improve effectiveness.